2022
DOI: 10.1038/s41598-022-19710-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genome-wide knockout mouse database identifies candidate ciliopathy genes

Abstract: We searched a database of single-gene knockout (KO) mice produced by the International Mouse Phenotyping Consortium (IMPC) to identify candidate ciliopathy genes. We first screened for phenotypes in mouse lines with both ocular and renal or reproductive trait abnormalities. The STRING protein interaction tool was used to identify interactions between known cilia gene products and those encoded by the genes in individual knockout mouse strains in order to generate a list of “candidate ciliopathy genes.” From th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Cilia-specific ubiquitinome analysis identified proteins that could regulate ESCRT-dependent clathrin-mediated endocytosis and caveolin 1-mediated cilia formation in murine inner medullary collecting duct 3 (IMCD3) cells and hTERT-RPE1 cells, respectively ( Aslanyan et al, 2023 ). In silico approach using the International Mouse Phenotype Consortium data and STRING, a database of known and predicted protein-protein interactions, have successfully found novel ciliopathy genes ( Higgins et al, 2022 ). Chemicals to regulate these ciliary genes could be generated using technologies that lead to targeted protein degradation, such as proteolysis-targeting chimeras and small-molecule hydrophobic tagging ( Bhole et al, 2023 ; Xie et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cilia-specific ubiquitinome analysis identified proteins that could regulate ESCRT-dependent clathrin-mediated endocytosis and caveolin 1-mediated cilia formation in murine inner medullary collecting duct 3 (IMCD3) cells and hTERT-RPE1 cells, respectively ( Aslanyan et al, 2023 ). In silico approach using the International Mouse Phenotype Consortium data and STRING, a database of known and predicted protein-protein interactions, have successfully found novel ciliopathy genes ( Higgins et al, 2022 ). Chemicals to regulate these ciliary genes could be generated using technologies that lead to targeted protein degradation, such as proteolysis-targeting chimeras and small-molecule hydrophobic tagging ( Bhole et al, 2023 ; Xie et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…A major new addition is the first integration of data from the International Mouse Phenotyping Consortium (IMPC) (Peterson and Murray 2022 ; Groza et al 2023 ) which includes the NIH Knock-out Mouse Phenotyping (KOMP) centers. Several recent studies have reported using KOMP knockout mice (Basilico et al 2022 ; Brommage and Ohlsson 2019 ; Cacheiro et al 2019 ; da Silva-Buttkus et al 2023 ; Higgins et al 2022 , and many others). The IMPC consortium has characterized thousands of single-gene deletion mutations on a wide array of phenotyping assays coordinated across centers.…”
Section: Current Contentsmentioning
confidence: 99%
“…For each knockout (KO) line, abnormal phenotypes are being ascertained across a range of physiological systems through comparison with wild-type lines ( Kurbatova et al, 2015 ; Haselimashhadi et al, 2020 ). These gene–phenotype associations have been investigated to increase our knowledge on human disease using multiple, complementary approaches: (1) to learn about sexual dimorphism and pleiotropic traits ( Karp et al, 2017 ; Munoz-Fuentes et al, 2022 ), (2) to reveal previously unidentified candidate genes for multiple physiological systems and disease types ( Higgins et al, 2022 ; Bowl et al, 2017 ; Chee et al, 2023 ; Cacheiro et al, 2022 , 2020 ) and (3) to investigate how well the current phenotypic screens capture specific human traits ( Cacheiro et al, 2023 ; Lindovsky et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%